2018
DOI: 10.1261/rna.067330.118
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of substrate recognition and specificity of tRNAHis guanylyltransferase during nucleotide addition in the 3′–5′ direction

Abstract: The tRNA guanylyltransferase (Thg1) transfers a guanosine triphosphate (GTP) in the 3'-5' direction onto the 5'-terminal of tRNA, opposite adenosine at position 73 (A). The guanosine at the -1 position (G) serves as an identity element for histidyl-tRNA synthetase. To investigate the mechanism of recognition for the insertion of GTP opposite A, first we constructed a two-stranded tRNA molecule composed of a primer and a template strand through division at the D-loop. Next, we evaluated the structural requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 58 publications
(74 reference statements)
2
20
0
Order By: Relevance
“…c). This type of highly specific modification enzymes also include the enzyme catalyzing the 2′‐O‐ribosyl phosphate addition to A64 in yeast initiator tRNA i Met , the tRNA His guanylyltransferase Thg1 that adds the G −1 residue unique to tRNA His , Dnmt2 that introduces the m 5 C38 modification specifically in tRNA Asp or tRNA Glu depending on the organism , and the acetyltransferase TmcA that introduces the ac 4 C34 modification in E. coli Elongator tRNA Met . The enzymes of this class are often highly sequence‐specific, such as for instance Tgh1 that adds the G −1 residue to tRNAs possessing a histidine GUG anticodon .…”
Section: Determinants Of Specificity In Trna Modification Enzymesmentioning
confidence: 99%
“…c). This type of highly specific modification enzymes also include the enzyme catalyzing the 2′‐O‐ribosyl phosphate addition to A64 in yeast initiator tRNA i Met , the tRNA His guanylyltransferase Thg1 that adds the G −1 residue unique to tRNA His , Dnmt2 that introduces the m 5 C38 modification specifically in tRNA Asp or tRNA Glu depending on the organism , and the acetyltransferase TmcA that introduces the ac 4 C34 modification in E. coli Elongator tRNA Met . The enzymes of this class are often highly sequence‐specific, such as for instance Tgh1 that adds the G −1 residue to tRNAs possessing a histidine GUG anticodon .…”
Section: Determinants Of Specificity In Trna Modification Enzymesmentioning
confidence: 99%
“…Crystallographic studies have revealed an elaborate network of contacts between RIG-I and the terminal base pair of 5 0 -triphosphorylated duplexes (Luo et al, 2012;Devarkar et al, 2016). In addition, host and pathogen RNA molecules present a diversity of different terminal sequences (Crary et al, 2003;Cantero-Camacho and Gallego, 2018;Nakamura et al, 2018;Herrera-Carrillo et al, 2017). It has therefore been of significant interest to determine whether there are base pair-recognition determinants for productive RIG-I binding and whether specific types of terminal base pairs are strongly preferred by the receptor.…”
Section: The Influence Of Terminal Base Pair Sequence On Rig-i Bindingmentioning
confidence: 99%
“…MaTLP assembles as a dimer-of-dimers similar to bona fide Thg1, yet uses a different mechanism of tRNA coordination. CaThg1 coordinates tRNA between both dimers of the tetramer, and binds Thg1–tRNA via 4:2 stoichiometry [54]. MaTLP independently binds one tRNA molecule per dimer, and does not seem to coordinate anticodon recognition by the opposing dimer, which is consistent with the notion of TLP repair activity (Figure 6) [23,40].…”
Section: Thg1-like Proteins Function In Trna Repairmentioning
confidence: 57%
“…DdiTLP3’s role in tRNA 5′-editing also utilizes 3′ to 5′ polymerase function, but to repair mt-tRNA that have been truncated at their 5′-ends due to the removal of one or more incorrectly base-paired nucleotides encoded in the precursor tRNA [49]. This 5′-end repair step is essential for D. discoideum , and likely for many other single-celled eukaryotes that similarly encode mt-tRNA with 5′-mismatches [34,47,49,50,51,52,53,54]. Presumably, the TLPs encoded by these species are capable of participating in 5′-editing, although the identity of specific enzymes that participate in this process has so far only been demonstrated in D. discoideum [32,33,41,42,43,44].…”
Section: Thg1-like Proteins Function In Trna Repairmentioning
confidence: 99%
See 1 more Smart Citation